French bean seed production calendar - Pham Thi, Huong Mai; Luong, Lam Van; Nguyen, Thi Phuong; Nguyen, Thi Tan Loc; Le Nhu, Thinh; Ngo, Thi Hanh; Nabuuma, Deborah Sandra; Stomph, Tjeerd-Jan; Swaans, Cornelis Petrus Maria (2021)
French bean seed production calendars for awareness creation and capacity building activities in vegetable and seed production and storage among ethnic minority vegetable farming households in Northern Vietnam. Particularly designed with and for the H’Mong and Dao people in Lao Cai province and Thai people in Son La province in English and Vietnamese.